2019
DOI: 10.1186/s12880-019-0307-7
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of nonmelanoma skin cancer using digital images: a systematic review

Abstract: Background Computer-aided diagnosis of skin lesions is a growing area of research, but its application to nonmelanoma skin cancer (NMSC) is relatively under-studied. The purpose of this review is to synthesize the research that has been conducted on automated detection of NMSC using digital images and to assess the quality of evidence for the diagnostic accuracy of these technologies. Methods Eight databases (PubMed, Google Scholar, Embase, IEEE Xplore, Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…Tschandl and colleagues admit that this algorithm is not ready to be implemented in the clinic, but the results of the study do demonstrate that CNNs are capable of more complex diagnoses and call for the collection of more dermoscopic and clinical images of rare malignant lesions. Marka et al [3] carried out a systematic review of 39 studies on the automated detection of NMSC and found that most studies report model performance greater than or equal to the reported diagnostic accuracy of the average dermatologist, but that relatively few studies have presented a high level of evidence.…”
Section: Non-melanoma Skin Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Tschandl and colleagues admit that this algorithm is not ready to be implemented in the clinic, but the results of the study do demonstrate that CNNs are capable of more complex diagnoses and call for the collection of more dermoscopic and clinical images of rare malignant lesions. Marka et al [3] carried out a systematic review of 39 studies on the automated detection of NMSC and found that most studies report model performance greater than or equal to the reported diagnostic accuracy of the average dermatologist, but that relatively few studies have presented a high level of evidence.…”
Section: Non-melanoma Skin Cancermentioning
confidence: 99%
“…Translational research in dermatology is already abundant, with data from the genome, epigenome, transcriptome, proteome, and microbiome, areas of research that are often referred to by the shortened term ''omics'' [2]. Recent advancements in faster processing and cheaper storage have allowed for the development of machine learning (ML) algorithms with human-like intelligence that have numerous applications in dermatology [3][4][5]. To assess the effectiveness of these emerging technologies, it is imperative that dermatologists have a basic understanding of artificial intelligence and ML.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, the inspiration is to accomplish consistency in a powerful range for a lot of information, flag, or pictures to stay away from mental interruption or exhaustion. [14] For instance, a paper will endeavor to make the entirety of the pictures in an issue share a comparative scope of grayscale.…”
Section: A Preprocessingmentioning
confidence: 99%
“…Gamma correction, or regularly basically gamma, is a nonlinear activity used to encode and interpret luminance or tristimulus values in video or still picture systems. [14] Gamma correction is, in the least complex cases, characterized by the accompanying force law articulation: = (2) where the non-negative genuine info esteem I in is raised to the power and duplicated by the consistent K, to get the yield esteem Iout. In the regular instance of K = 1, information sources and yields are commonly in the range 0-1.…”
Section: B Gamma Correctionmentioning
confidence: 99%
“…But still, several challenges exist which decreased the accuracies of these automated systems. In general, a simple automated system follows these steps: preprocessing of original data, detection of the lesion through segmentation or featuresbased techniques, and finally classification by extracting patterns information (Jadooki, Mohamad, Saba, Almazyad, & Rehman, 2016;Majumder & Ullah, 2019;Marka, Carter, Toto, & Hassanpour, 2019;Sharif et al, 2017). A lot of techniques are presented for contrast enhancement in this domain to improve the visual quality of lesion in the given images.…”
mentioning
confidence: 99%